Description of a new neotropical species of Xiqilliba Kramer (Hemiptera: Cicadellidae: Neocoelidiinae) - Marques, Ana Paula Coelho; Ale-Rocha, Rosaly (Zootaxa, 2017)
Xiqilliba Kramer is revised, and a new species, Xiqilliba sakakibarai sp. nov. is described and illustrated. The type species of the genus, Xiqilliba bellator Kramer, is redescribed. The new species can be differentiated from X. bellator by the morphology of the male genitalia, especially by: (1) shorter quadrangular pygofer with bifurcated apical lobe; (2) long and slender style with strong basal curvature; (3) enlarged aedeagus with two pairs of apical processes; and (4) anal tube with pair of short processes of rounded apices. A generic diagnosis and redescription are provided, as well as illustrations of Xiqilliba species.